The Role of Monusco through the Indonesian Army Engineering Company (Kompi Zeni TNI AD) in Conflict Resolution in the Democratic Republic of the Congo - Zulham, Muhammad; Darmawan, Harry (JURNAL TAPIS, 2025)
This study analyzes the role of the Indonesian Army Engineer Company (Kompi Zeni TNI AD) – Garuda Contingent in MONUSCO in the United Nations peacekeeping mission under MONUSCO (United Nations Organization Stabilization Mission in the Democratic Republic of the Congo). The research focus is directed at the contribution of this unit in supporting security sector reforms and post-conflict development in Beni Province, Democratic Republic of Congo (DRC). This study fills a research gap related to the involvement of Indonesian military engineering units in peace missions, which has so far highlighted more aspects of diplomacy and infantry forces. The method used is descriptive qualitative with in-depth interview techniques, field observations, and documentation studies. Primary data were obtained through the direct experience of Zeni Company Task Force personnel in the field, while secondary data came from MONUSCO reports, UN publications, and academic literature. The analysis was carried out through data reduction, presentation, and triangulation verification to ensure the validity of the findings. The results of the study show that the TNI AD Zeni Company plays an important role in the development of strategic infrastructure such as the Beni-Eringeti-Kainama road and the Halulu bridge, which have a real impact on improving the security, mobility, and welfare of the local community. These findings confirm that the participation of the Zeni Company not only strengthens the effectiveness of MONUSCO's mandate in civilian protection, but also strengthens Indonesia's defense diplomacy and demonstrates a model of military-civilian synergy in realizing sustainable peace in Africa.